Secondary traumatic stress and coping: a case study of the social workers employed at the South African Police Service - Masson, Francine Julia (My University, 2016)
South Africa is regarded as one of the most violent countries in the world. Colonialism and apartheid laid the foundations for a divided and segregated society where violence was accepted as a legitimate means of conflict resolution in order to ensure the domination of one racial group over all other groups. As social and economic inequalities have become more entrenched in South African society, criminal violence has escalated. However, the nature of violence in the country has changed from political violence to criminal violence. Against this backdrop of violence and associated trauma, the South African Police have the insurmountable task of trying to maintain law and order. The science of traumatology is a burgeoning field; traditionally empirical research has focused on the responses of primary trauma victims. However, in recent decades the secondary effects of traumatisation on those who counsel the victims of primary trauma, has received significant attention. Located within the South African Police Service, is an often forgotten secondary group of professionals who assist the police officials through assuming the roles of occupational and forensic social work. The profession of social work is inherently stressful and demanding, especially in a country like South Africa, where social problems are ubiquitous and pervade every facet of South African society. Furthermore, a particular occupational stressor significantly impacting on these social workers as they investigate child abuse or provide counselling for a police officer, is secondary traumatisation. The questions arise: firstly, how these social workers are affected by the amount of traumatic material to which they are exposed by the very nature of their work, and secondly, what coping strategies they employ. It was therefore deemed imperative to explore the effects of secondary traumatisation experienced by these social workers in the South African Police Service in order to understand and ameliorate the negative effects of secondary traumatic stress. Furthermore, social work supervisors can enhance the quality of care their social workers provide to clients if they are adequately supported. It was therefore also considered necessary to explore the stressors these social workers experience and to identify the necessary support mechanisms appropriate to such therapeutic endeavors. The primary aim of this study was therefore to explore the nature and extent of secondary traumatic stress experienced by social workers employed by the South African Police Service. The research design adopted for this study was exploratory, descriptive and correlational, while the research methodology employed was a hybrid of both quantitative and qualitative paradigms. As this study involved an in-depth analysis of a bounded system comprising social workers employed at SAPS, the research was considered a case study. The study comprised two phases: In the first phase questionnaire booklets containing seven standardised research tools and open-ended questions, were administered in group settings. In addition, questionnaires were posted to social workers who were not able to attend the group meetings along with a self-addressed envelope. The research tools measured the nature of secondary trauma exposure, levels of secondary traumatic stress, vicarious trauma, compassion satisfaction, burnout, coping resources and dimensions of the work environment. Two hundred questionnaire booklets were distributed and 128 usable questionnaires were returned. Descriptive and inferential statistics were used to analyse the quantitative data, through the use of statistical programmes, SAS and SPSS. In the second stage of the study, 30 participants who participated in the first part of the study and who indicated that they were willing to be interviewed, were purposively selected. A structured research tool was used to guide the interview in order to explore the participants’ perceptions and experiences of secondary trauma while working for SAPS. The interviews were conducted either face-to face, telephonically or through Skype. The qualitative data that emerged from the interviews were analysed through the use of Atlasti, a qualitative computer programme, which assisted the researcher in the thematic analysis. Through the process of incorporating qualitative techniques, the researcher also made use of reflexivity when analysing the qualitative data. In total 128 social workers participated in the study, of whom 102 were occupational social workers while 26 were forensic social workers, all located within South Africa. The extent of exposure to secondary trauma varied substantially between both occupational and forensic social work when considered as separate divisions, as well as within each discipline. This variation manifested in frequencies and duration of cases. In the interviews forensic social workers identified particularly traumatic cases as those where the sexual abuse was severe or the child had died as a result of extreme abuse. In comparison, occupational social workers identified some of the worst cases they had dealt with as cases where the police officers became disabled; and where they were required to deal with police suicides and police family murders or femicide-suicides. Most participants presented with high or average levels of secondary traumatic stress and vicarious trauma as well as with moderate and low levels of burnout. Furthermore, there was a strong positive correlation between levels of secondary traumatic stress and burnout. The majority of participants experienced average levels of compassion satisfaction from their work. Participants identified various coping strategies and resources incorporating different individual dimensions, namely, physical, emotional, cognitive, social and spiritual. Participants showed high levels of resilience and findings indicated that resilience was negatively correlated with vicarious trauma. There were numerous significant differences between the different ranks of the participants. Participants of higher rank reported greater trauma exposure and had significantly higher secondary traumatic scores. Coloured participants experienced significantly lower levels of vicarious traumatisation than Black participants. Furthermore, there were numerous statistically significant differences apparent between the forensic and occupational social workers. Forensic social workers manifested significantly higher levels of vicarious trauma than occupational social workers, and forensic social workers had greater distortions regarding self-intimacy than occupational social workers. In addition, forensic social workers presented with lower coping resources and lower levels of resilience than occupational social workers. Participants also experienced below average levels of satisfaction within the work environment at SAPS. The results from the work environment scale showed that in particular the relationship aspects in the work environment were problematic and that colleague support levels were below average. There were also significant differences in work satisfaction levels between Black and White participants. These findings enhance understanding of trauma in racially polarised societies. Multivariate analysis revealed the complex relationships existing between the numerous variables in the study, further contributing to the theory of trauma in divided societies. Two structural equation models were developed to show the relationships of the variables measured in the study which were identical apart from the vicarious trauma variable which was separated to incorporate beliefs about self and beliefs about others. The models revealed that coping mechanisms moderated the relationship between traumatic stress exposure and vicarious trauma (self) and that such mechanisms moderated the resilience and burnout relationship. These findings of the study highlight the need to involve social workers at SAPS in the drafting and implementation of a self-care policy which would help to promote empowerment and responsibility of social workers for their own mental health. Recommendations for social work policy, education, practice, supervision and support as well as future research are also provided.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy. February 2016
Keywords: Social workers--Job stress--South Africa; Psychic trauma (Psychology); South African Police Service